If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -60 = 3 + 9x Solving -60 = 3 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -60 + -9x = 3 + 9x + -9x Combine like terms: 9x + -9x = 0 -60 + -9x = 3 + 0 -60 + -9x = 3 Add '60' to each side of the equation. -60 + 60 + -9x = 3 + 60 Combine like terms: -60 + 60 = 0 0 + -9x = 3 + 60 -9x = 3 + 60 Combine like terms: 3 + 60 = 63 -9x = 63 Divide each side by '-9'. x = -7 Simplifying x = -7
| (3x^2)-5x-7=0 | | (2x^2)+8x=0 | | 1+x^2=0 | | (2x^2)-7x-1=0 | | 27a^3x^4-8x=0 | | 8+2x=x+40 | | 3y+24+6-2=33 | | -28+4=0 | | ln(x+1)ln(x)+ln(x^2)=1 | | ln(x+a)ln(x)+ln(x^2)=1 | | 53-2x=5x | | 11x-10=54 | | 6p^2+25-119=0 | | (6a^3+6a^2-7)+(5a^3-6a+8)= | | 2x^2-45=0 | | y+24y+144= | | 8a+12b+4= | | 9x+12y+15= | | 6a-18b+12c= | | 12a-28b+10c= | | 40=5w-15 | | 7x-7y-7z= | | 5x-5y+10z= | | 4d^2+29d-60=0 | | 45r^2-5=0 | | 45r^2-5=f | | 25x^2+16=y | | 6x(x-2)=0 | | y^3=144y | | 4x^2+4x-32=0 | | 9(a+b)= | | 3x^2+12x+36=0 |